Institutional frameworks and labor market performance: Comparative views on the U.S. and German economies - Friedrich Buttler; Wolfgang Franz; Ronald Schettkat; David W. Soskice (Routledge, 1995)
Institutional Frameworks and Labor Market Performance produces an in-depth analysis of the functioning of various labor market institutions in both the USA and Germany. Particular emphasis is given to the substantial differences between the US and Germany in the ways important areas are regulated. The authors show that the impact of institutions on economic performance is ambivalent. They argue that in this sense, the decision is not one between regulation and deregulation but rather one between different degrees and forms of regulation.
Keywords: 330; Arbeitsmarkt; Berufsbildung; Arbeitsbeziehungen; Lohn; Arbeitszeit; USA; Deutschland